What constitutes an Islamic retailer? Islamic store attributes from the prespectives of Islamic marketing principles - Abu Bakar, Abdul Rahim; Hussin, Siti Rahayu (Access Press UK, 2013)
An upcoming trend that has caught the attention of marketers and consumers alike is the recent debut of retailers that projected itself as an Islamic retailer. This paper provides a critical overview of the existing scholarship on the influence of Islam specifically towards consumer retail store selection. This paper outlined the general store attributes of an Islamic retailer based on the synthesis of past literatures. As the store image or “store personality” is determined as one of the factors of store choice, which is largely based on the store attributes, it is pertinent for retailers to project the “appropriate” Islamic store image in the minds of consumers.